Osteoporosis - (:unkn) unknown (My University, 1999)
Osteoporosis represents the most common form of metabolic bone disease. Its epidemiology, pathogenesis, clinical manifestations, radiographic and laboratory features, bone density measurements, and treatment are discussed.
Keywords: Bisphosphonates; Bone mineral density; HRT; Postmenopausal osteoporosis